The Influence of Perceived Risk and Perceived Benefits on Continuance Intention to Adopt Fintech P2P Lending Mediated by Trust in Indonesia - Purnama, Elang Satriaputra; Suryadi, Nanang; Andarwati, Andarwati (Profesional Muda Cendekia Publishing, 2023)
This study investigates the influence of perceived risk and perceived benefits on the continuance intention to adopt fintech P2P lending platforms in Indonesia, considering trust as a mediating factor. With the fintech sector experiencing rapid expansion, understanding the determinants of user retention is crucial for sustaining growth and ensuring consumer protection under the oversight of regulatory bodies like Otoritas Jasa Keuangan (OJK). A total of 105 participants were recruited for the survey, ensuring a diverse demoghparic representation in terms of age, gender, job, origin, and job occupation. The data were analyzed using Structrual Equation Modeling (SEM). The anaylis of the data revealed that perceived risk significantly gives negative influenced to continuance intention to adopt fintech p2p lending. In contrast, perceived benefit had a robust positive effect on continuance intention to adopt fintech p2p lending. Trust was found to partially mediate the relationship between perceived risk, perceived benefits, and continuance intention.